Prognostic value of negative stress cardiac magnetic resonance imaging in patients with moderate-severe coronary artery stenosis - Haney, Ailís Ceara; Salatzki, Janek; Hund, Hauke; Friedrich, Matthias G.; Giannitsis, Evangelos; Frey, Norbert; Steen, Henning; Loßnitzer, Dirk; Riffel, Johannes; André, Florian (Frontiers in Cardiovascular Medicine, 2023)
This study sought to evaluate the prognostic value of stress cardiac magnetic resonance (CMR) without inducible ischemia in a real-world cohort of patients with known severe coronary artery stenosis. The prognosis of patients with severe coronary artery stenosis and without inducible ischemia using stress CMR remains uncertain, even though it is excellent in identifying functionally significant coronary artery disease (CAD). Patients who underwent stress CMR between 02/2015 and 12/2016 without inducible ischemia and known CAD were retrospectively included. Patients were divided into two groups (group 1: 50–75% stenosis, group 2: >75% stenosis). The primary endpoint was defined as the occurrence of a major adverse cardiovascular event (MACE) (cardiac death, non-fatal myocardial infarction (MI), percutaneous coronary intervention (PCI), or coronary artery bypass grafting (CABG)). Real-world data from 169 patients were included (69 (60–75) years). Median follow-up was 5.5 (IQR 4.1–6.6) years. Events occurred after a mean time of 3.0±2.2 years in group 1 and after 3.7±2.0 years in group 2 (p = 0.35). Sixteen patients (18.8%) in group 1 and 23 (27.4%) in group 2 suffered from MACE without a significant difference between the groups (p = 0.33). In group 2, one cardiac death (1.2%), seven non-fatal MI (8.3%), fifteen PCI (17.9%), and one CABG (1.2%) occurred. The findings of this pilot study imply that long-term outcomes in a real-world patient cohort with known severe and moderate coronary artery stenosis but without inducible ischemia were similar. Stress CMR may provide valuable risk stratification in patients with angiographically significant, but hemodynamically non-obstructive coronary lesions.